Activation of a particulate Ta3N5 water-oxidation photoanode with a GaN hole-blocking layer. Issue 1 (27th October 2017) - Asakura, Yusuke; Higashi, Tomohiro; Nishiyama, Hiroshi; Kobayashi, Hiroyuki; Nakabayashi, Mamiko; Shibata, Naoya; Minegishi, Tsutomu; Hisatomi, Takashi; Katayama, Masao; Yamada, Taro; Domen, Kazunari
Abstract : The introduction of GaN as a hole-blocking layer for a particulate Ta3 N5 photoelectrode led to the enhancement of photoelectrochemical water oxidation. Abstract : Particulate Ta3 N5, a material that responds to visible light for photoelectrochemical O2 evolution, was glued to a metallic GaN conducting layer. The electrode was able to oxidize water with 1.8-fold higher efficiency than that without GaN. The GaN layer blocked the hole current from Ta3 N5 to the back-contact metal layer and prevented hole–electron recombination.